Analisis Hubungan Antara Kualitas Layanan Dengan Kepuasan Dan Loyalitas Mahasiswa Di PTS “X” - Sofiati, Sofiati (JURNAL RISET MANAJEMEN SEKOLAH TINGGI ILMU EKONOMI WIDYA WIWAHA PROGRAM MAGISTER MANAJEMEN, 2017)
The objective of this study is to test the relationship beetween quality service with customer satisfaction and loyalty .The subject matter we addressed three research questions. The first was: is quality quality service positif relatonship with customer satisfaction? The second research question addressed was: is customer satisfaction positif relationship with customer loyalty?Our the third research question was: is quality service positif directly with customer loyalty? Quality service is measured with SERVQUAL in five dimensions: tangibles, reability, responsiveness,assurance, and empathy.The population covers 800 students PTS “X”, while the taken sample was 210 students PTS “X”. The sample that used in this study is master of management student in management program and accounting program in PTS “X”. The data were analyzed by using Structural Equation Modelling (SEM). Empirical evidence supports the first hypothesis that the quality of service (Service Quality) consisting of; physical evidence, reliability, responsiveness, assurance, and empathy have a significant positive relationship with satisfaction. With the increasing quality of service provided by the management of PTS “X” then will also increase student satisfaction. Empirical evidence does not support the two hypothesis that Satisfaction has a positive relationship with Loyalty. This conclusion means that students who feel satisfaction does not necessarily have a sense of loyalty to the alma mater. Empirical evidence does not support the three hypothesis that states Quality has a positive relationship with Loyalty. This conclusion means that to increase customer loyalty, it is not enough to only pay attention to the quality of services, but more important is to increase customer satisfaction.